GASEKO: Scramble Game Media to Increase Elementary School Students’ Learning Independence - Darmayanti, Ni Kadek Eka Budi; Suarjana, I Made (Journal for Lesson and Learning Studies, 2024)
The lack of diversity in digital media and the low degree of student learning independence in primary schools prompted this development inquiry. In order to help fourth graders become more self-reliant learners, this study seeks to develop a realistic, practical, and successful economic scramble game (GASEKO) for classroom usage. The goal of this research was to analyze the extent to which fourth grade primary school pupils were able to learn independently, and the subjects’ included students, learning technology experts, and subject matter experts. The five-stage ADDIE model—which is used in this development study—consists of the following steps: analysis, design, development, implementation, and evaluation. A questionnaire or surveys are the tools utilized for gathering information. Fifteen primary school pupils in the fourth grade participated in the product trial. Qualitative, quantitative, and statistical descriptive analytic methods were employed to examine the study data. We can conclude that GASEKO media is a viable, practical, and effective strategy for enhancing the learning independence of fourth graders based on the following evidence: (1) GASEKO media has strong credentials from expert validation; (2) GASEKO media has very good credentials according to student responses; and (3) GASEKO media significantly impacts fourth graders' learning independence. This study's findings suggest that GASEKO media can broaden the range of educational resources available to schools, leading to more engaging and effective lessons for students.